A FIGURATIVE LANGUAGE ANALYSIS OF SONG LYRIC ‘MIRRORS’ BY JUSTIN TIMBERLAKE - Bejo Sutrisno; Amanda Putri (Journal of English Language and Literature (JELL), 2017)
The purposes of this study are to know the kinds of figurative language and the general meaning used in selected lyrics of Justin Timberlake song. This research is designed to identify some figurative language by understanding the general meaning when they are used in the song lyric. The technique of descriptive analysis is used to analyze data of the figurative language used in the lyric of the ‘Mirror’. Based on research findings, the writers found some figurative languages in the Justin Timberlake’s selected song. It can be found that most of figurative languages which are used in lyrics of Justin Timberlake’s selected songs are “symbol, metaphor, personification and simile” that have a great exaggeration used to emphasize a point, used for expression or comic effect.